Analisis Faktor-faktor yang Mempengaruhi Permintaan Emas di Indonesia 2020-2024 - Farida Nur Azizah; Nurjannah Rahayu Kistanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the factors that influence the demand for gold. Gold is considered a safe investment amid economic instability and inflation, which is relevant to the research findings that show that investors choose gold during high inflation. This study aims to develop a model that can predict the demand for gold by considering monetary policy, with international conditions and to develop guidelines for investors who want to balance their portfolios with gold in the face of market risks caused by oil price fluctuations, changes in stock market indices, and monetary policy. The analysis used is linear regression analysis with the Eviews program. The results of this study showed that there is a significant influence of GDP per capita, gold prices, and BI Rate on the demand for gold. These three variables have a positive influence, which means that the higher the GDP per capita, gold prices, and BI Rate, the higher the demand for gold, and vice versa, the lower the GDP, the lower the demand for gold. The results of this study also showed that there was no influence of silver prices and exchange rates on the demand for gold.